PERMAINAN TRADISIONAL DALAM MENINGKATKAN KECERDASAN EMOSI - Suriah Hanafi (EDU RESEARCH, 2023)
The background of this research is that emotional intelligence is a child's ability to motivate themselves and withstand frustration, be able to control impulses and not exaggerate pleasure, be able to regulate mood and keep stress from paralyzing the ability to think, be able to empathize and always pray. This research aims to determine the increase in students' emotional intelligence through traditional games. Data collection was carried out by conducting observations, interviews, documentation, and using questionnaires. Data analysis is carried out by giving meaning to the data that has been collected and from this data conclusions can be drawn. The method used in this research is the experimental method. The sample used was 35 students at SD IKIP UNM Makassar. The research results found a Sig value. = 0.000 < 0.05, so it can be concluded that traditional games have an influence on increasing students' emotional intelligence.